EXPRESSION OF ISLAMIC VIEWS IN THE WORK “KUTADGHU BILIG” (TAMADDUN NURI JURNALI, 2024)
In this article, Yusuf Khos Hajib created his work "Kutadgu Bilig" in the spirit of admonition, perfection and mysticism. Also, the introduction of the work with hamd (i.e. praise of God) and na't (i.e. praise to the prophets) proves that the spirit of Islam is instilled in the beginning and the end of the work, and that a number of terms related to theology are used in "Kutadgu Bilig".